2003
DOI: 10.1136/bjo.87.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical endonasal dacryocystorhinostomy with mucosal flaps

Abstract: Aims: To describe and assess the efficacy of mechanical endonasal dacryocystorhinostomy (MENDCR). This is a new technique that involves creation of a large rhinostomy and mucosal flaps. The study involved a prospective nonrandomised interventional case series with short perioperative follow up. Method: A prospective series of 104 consecutive endonasal DCRs performed from January 1999 to December 2001 were entered into the study. Patients included in the study had nasolacrimal duct obstruction and had not had p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
58
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(63 citation statements)
references
References 34 publications
4
58
1
Order By: Relevance
“…These points argue for need for further research and investigation to clearly establish the efficacy of stenting in endoscopic DCR. We could demonstrate a high surgical success rate without using other post-op preventive procedures like use of antimetabolites like mitomycin C [17] or marsupialization of the sac on the lateral nasal wall [18][19][20] which have been incorporated by other investigators. Four out of 90 patients in our study had no symptomatic relief despite achieving anatomical patency.…”
Section: Discussionmentioning
confidence: 99%
“…These points argue for need for further research and investigation to clearly establish the efficacy of stenting in endoscopic DCR. We could demonstrate a high surgical success rate without using other post-op preventive procedures like use of antimetabolites like mitomycin C [17] or marsupialization of the sac on the lateral nasal wall [18][19][20] which have been incorporated by other investigators. Four out of 90 patients in our study had no symptomatic relief despite achieving anatomical patency.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to other studies where all included patients underwent formal preoperative imaging. 19 Our study was limited by a relatively short follow-up period. However, a number of studies have shown that changes within the newly created ostium following END-DCR are minimal beyond 4 weeks postoperatively and that late failure is relatively uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical 14 and surgical 6 studies have suggested the unciform process as adjacent and posterior to the lachrymal fossa. Tsirbas and Wormald 19 stated that such structure must be preserved during DCR-en. Fayet 20 et al found some degree of unciform process overlapping the lachrymal fossa in 94.8% of the cases.…”
Section: Discussionmentioning
confidence: 99%